Ascorbate Alleviates Fe Deficiency-Induced Stress in Cotton (Gossypium hirsutum) by Modulating ABA Levels - Guo, Kai; Tu, Lili; Wang, Pengcheng; Du, Xueqiong; Ye, Shue; Luo, Ming; Zhang, Xianlong (Frontiers in Plant Science, 2017)
Fe deficiency causes significant losses to crop productivity and quality. To understand better the mechanisms of plant responses to Fe deficiency, we used an in vitro cotton ovule culture system. We found that Fe deficiency suppressed the development of ovules and fibers, and led to tissue browning. RNA-seq analysis showed that the myo-inositol and galacturonic acid pathways were activated and cytosolic APX (ascorbate peroxidase) was suppressed in Fe-deficient treated fibers, which increased ASC (ascorbate) concentrations to prevent tissue browning. Suppression of cytosolic APX by RNAi in cotton increased ASC contents and delayed tissue browning by maintaining ferric reduction activity under Fe-deficient conditions. Meanwhile, APX RNAi line also exhibited the activation of expression of iron-regulated transporter (IRT1) and ferric reductase-oxidase2 (FRO2) to adapt to Fe deficiency. ABA levels were significantly decreased in Fe-deficient treated ovules and fibers, while the upregulated expression of ABA biosynthesis genes and suppression of ABA degradation genes in Fe-deficient ovules slowed down the decreased of ABA in cytosolic APX suppressed lines to delay the tissue browning. Moreover, the application of ABA in Fe-deficient medium suppressed the development of tissue browning and completely restored the ferric reduction activity. In addition, ABA 8’-hydroxylase gene (GhABAH1) overexpressed cotton has a decreased level of ABA and shows more sensitivity to Fe deficiency. Based on the results, we speculate that ASC could improve the tolerance to Fe deficiency through activating Fe uptake and maintaining ABA levels in cotton ovules and fibers, which in turn reduces symptom formation.